Error estimates for a neumann problem in highly oscillating thin domains - Pereira, Marcone C.; Silva, Ricardo P. [UNESP] (American Institute of Mathematical Sciences (AIMS), 2013)
In this work we analyze the convergence of solutions of the Poisson equation with Neumann boundary conditions in a two-dimensional thin domain with highly oscillatory behavior. We consider the case where the height of the domain, amplitude and period of the oscillations are all of the same order, and given by a small parameter e > 0. Using an appropriate corrector approach, we show strong convergence and give error estimates when we replace the original solutions by the first-order expansion through the Multiple-Scale Method.
Keywords: Correctors; Error estimate.; Homogenization; Thin domains